Assessment of biosafety aspects during procedures of genetic transformation of plants - Petiukh, G.P.; Karachinska, N.V. (Problems of Environmental Biotechnology, 2021)
The article discusses the possibility of risks of uncontrolled gene transfer during procedures of plant genetic transformation, which is an integral part of the system of biosafety of the use of genetically modified organisms in their release into the environment. In order to test this phenomenon, the authors conducted research to study the likelihood of such transfer of genes from genetic constructs found in cells of bacterial strains used to transform plants, in particular Agrobacterium tumefaciens, in the form of plasmid DNA and determine tolerance to antibiotics and other bacteria cells, in particular Pseudomonas fluorescens. Bacterial cells with cross-tolerance to antibiotics were obtained in the experiments, which suggest the presence of the phenomenon of gene transfer by a horizontal mechanism. The obtained result suggests the possibility of unpredictable consequences in the agroecosystems as a result of gene drift from genetic constructs to soil microbiota.